A Beautiful Windup - Choudhary, Neelam Maansingh (National School of Drama, New Delhi, 2023)
A Beautiful Windup is a direction scenework presented by the Third Year Direction and Design students of the National School of Drama. The production was designed and directed by Paski under the guidance of Neelam Maansingh Choudhary with assistant guidance from Vansh Bhardwaj. Floor management was handled by Mrinali Pandey and Rajkishore Sahu, while Shruthi V. was responsible for music execution.
Neelam Maansingh Choudhary is one of India's most distinguished theatre directors, known for integrating traditional Indian performance traditions with contemporary theatre practices. As the production guide, she supervised the artistic and pedagogical development of the scenework. Paski is a theatre practitioner and a Third Year Direction and Design student at the National School of Drama. For A Beautiful Windup, Paski served as both the designer and director, demonstrating practical skills in conceptualization, staging, visual composition, and actor direction under the mentorship of senior theatre professionals.
Keywords: Direction Scenework; Theatre Direction; Stage Performance; Experimental Theatre; Contemporary Theatre; Performance Studies; Theatre Education